Autoimmune gastritis with a gastric hamartomatous inverted polyp and two hyperplastic polyps: a case report. Issue 3 (March 2023) - Hou, Jun-zhen; Dong, Ning-ning; Yue, Bing; Meng, Fan-dong; Wang, Yong-jun
We report an unusual case of autoimmune gastritis (AIG) complicated with a submucosal tumor (SMT) and two pedunculated polyps in a 60-year-old man. The patient was admitted for epigastric distention, heartburn, and anorexia. Endoscopy showed an SMT in the fundus, two pedunculated polyps in the body, and markedly atrophic mucosa of the body and fundus. The SMT, measuring 20 mm in diameter, was resected by endoscopic submucosal dissection and histologically diagnosed as a gastric hamartomatous inverted polyp (GHIP), which is characterized by submucosal glandular proliferation, cystic dilatation, and calcification. The gland structures consisted of foveolar cells and pseudopyloric or mucous-neck cell types. The two pedunculated polyps that were resected by endoscopic mucosal resection were histologically diagnosed as hyperplastic polyps, which are characterized by hyperplastic foveolar glands with pseudopyloric or mucous-neck glands in the inflamed stroma in the mucosa, which consisted of almost the same types of lining cells as the GHIP in the fundus. Findings may indicate the relationship between GHIP, hyperplastic polyp, and AIG. We highlight considering GHIP as a differential diagnosis for an SMT in patients with AIG.